2008
DOI: 10.1016/j.jmb.2007.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitor for Prolyl Tripeptidyl Aminopeptidase from Porphyromonas gingivalis and Details of Substrate-recognition Mechanism

Abstract: Prolyl Tripeptidyl Aminopeptidase from P. gingivalis 2 SummaryA new inhibitor, H-Ala-Ile-pyrrolidin-2-yl boronic acid, was developed as an inhibitor against prolyl tripeptidyl aminopeptidase with the K i value of 88.1 nM. The structure of the prolyl tripeptidyl aminopeptidase complexed with the inhibitor (enzyme-inhibitor complex) was determined at 2.2 Å resolution. The inhibitor was bound to the active site through a covalent bond between Ser603 and the boron atom of the inhibitor. This structure should close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…However, distances of 3.8 Å ( T. brucei TR) and 4.0 Å ( T. cruzi TR) between the oppositely charged atoms indicate a long‐range Coulombic interaction rather than a strong charge‐assisted hydrogen bond. This correlates with the observation of an only 3.5‐fold increased K ic value of the Glu 18 Ala mutant relative to the wild‐type enzyme 53. In both TR species, Glu 467′ is not involved in binding.…”
Section: Resultssupporting
confidence: 83%
“…However, distances of 3.8 Å ( T. brucei TR) and 4.0 Å ( T. cruzi TR) between the oppositely charged atoms indicate a long‐range Coulombic interaction rather than a strong charge‐assisted hydrogen bond. This correlates with the observation of an only 3.5‐fold increased K ic value of the Glu 18 Ala mutant relative to the wild‐type enzyme 53. In both TR species, Glu 467′ is not involved in binding.…”
Section: Resultssupporting
confidence: 83%
“…These two glutamates resemble the double–Glu motifs found in Dipeptidyl peptidase IV22, Tricorn factor F123 and Prolyl–tripeptidylpeptidase24,25 which coordinate the positively charged N–terminus of peptide substrates via ionic interactions. Therefore, we mutated either of the two glutamates into glutamine residues to probe their potential interaction with the substrate and found that both substitutions lead to a drastic increase in K M and decrease of the cleavage rate (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 89%
“…This is a recurrent structural principle among aminopeptidases and the two glutamate residues appear to form the double–Glu motif that has emerged as the prevailing motif for imparting aminopeptidase activity on peptidases, such as Dipeptidylpeptidase IV22, Aminopeptidase N32, and Aminopeptidase F123. Among tripeptidyl peptidases, this motif has recently been described in prolyl tripeptidyl aminopeptidase from Porphyromonas gingivalis24,25. Based on homology to this peptidase, the double–Glu motif had been suggested to be present in TPP II33.…”
Section: Discussionmentioning
confidence: 99%
“…Our models suggest that SpAAP is deprived of these covalent interactions, pointing out another structural determinant of the cold adaptation of SpAAP. A lack of disulphide bridges in favour of free cysteines is also observed in the structures of mesophilic AAPs, such as Streptomyces morookaense (PDB entry 3AZO [43]) and Phorphyromonas gingivalis AAPs (PDB entry 2Z3Z [53]). …”
Section: Distribution Of the Cysteine Residuesmentioning
confidence: 79%